Obesity trajectories and risk of dementia: 28 years of follow-up in the Whitehall II Study - Singh-Manoux, Archana (Alzheimers Dement, 2018)
INTRODUCTION: We examined whether obesity at ages 50, 60, and 70 years is associated with subsequent dementia. Changes in body mass index (BMI) for more than 28 years before dementia diagnosis were compared with changes in BMI in those free of dementia. METHODS: A total of 10,308 adults (33% women) aged 35 to 55 years in 1985 were followed up until 2015. BMI was assessed six times and 329 cases of dementia were recorded. RESULTS: Obesity (BMI ≥30 kg/m(2)) at age 50 years (hazard ratio = 1.93; 1.35–2.75) but not at 60 or 70 years was associated with risk of dementia. Trajectories of BMI differed in those with dementia compared with all others (P < .0001) or to matched control subjects (P < .0001) such that BMI in dementia cases was higher from 28 years (P = .001) to 16 years (P = .05) and lower starting 8 years before diagnosis. DISCUSSION: Obesity in midlife and weight loss in the preclinical phase characterizes dementia; the current obesity epidemic may affect future dementia rates.